2014
DOI: 10.1039/c4cc00251b
|View full text |Cite
|
Sign up to set email alerts
|

Unusual formation of a N-heterocyclic germylene via homolytic cleavage of a C–C bond

Abstract: Reaction of the monoanionic radical salt IP˙(-)K(+) (IP = (Py)CH(=NR); Py = C5H4N, R = 2,6-iPr2C6H3; α-iminopyridine) with GeCl2(dioxane) afforded compound (IPGeCl)2 (1) which produced red blocks of IPGe: (2), when treated with KC8 in toluene. 1 is a digermylene formed via C-C coupling between two carbon-centered radicals. 2 can be considered as an analogue of a N-heterocyclic carbene, which exhibits a five-membered GeC2N2 ring with one C=C double bond. 2 is formed by two-electron reduction of 1 with cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Additionally, the smaller g-value implies the increased tetrahedral character of the germyl radical geometry, although all of the hfc values are in a very narrow range. The g-value for 4 (g = 1.9988) was close to those for 5a (1.9986), Scheme 2 (a) Germyl radicals (4) bonded to three nitrogen atoms formed from the reaction of 1a and 2 (100 : 60 molar ratio), and (b) germyl radicals (5) bonded to two nitrogen atoms and one oxygen atom. 10 3 (1.9991), suggesting that these four radicals have a similar geometry on the centered germanium.…”
Section: Esr Studymentioning
confidence: 77%
See 1 more Smart Citation
“…Additionally, the smaller g-value implies the increased tetrahedral character of the germyl radical geometry, although all of the hfc values are in a very narrow range. The g-value for 4 (g = 1.9988) was close to those for 5a (1.9986), Scheme 2 (a) Germyl radicals (4) bonded to three nitrogen atoms formed from the reaction of 1a and 2 (100 : 60 molar ratio), and (b) germyl radicals (5) bonded to two nitrogen atoms and one oxygen atom. 10 3 (1.9991), suggesting that these four radicals have a similar geometry on the centered germanium.…”
Section: Esr Studymentioning
confidence: 77%
“…[1][2][3][4][5] In the polymerization chemistry field, there are few examples of their use as a monomer or a catalyst (initiator) because of the difficulty faced in handling them, such as inducing self-oligomerization, such difficulties are caused by the compounds' instability. Germylenes have a strong reducing ability and are generally observed as a short-lived reaction intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly shown by the behaviour of Au nanorods entrapped in an ORMOSIL obtained from 3-mercaptopropyl trimethoxysilane (MPS) and TEOS. [16] Employing an irradiation beam of 5.0 ns laser pulses at 532 nm, the ORMOSIL glass sheet (1.5 cm diameter and 2 mm thickness) doped with 0.192% Au nanorods showed both excellent optical limiting effect and high damage threshold ( Figure 1).…”
Section: Enhanced Stable Activitymentioning
confidence: 99%
“…Noting the importance of protection materials against the laser damage, the team concluded that this nanocomposite material is a promising candidate for optical limiter, especially due to the enhanced thermal stability of the ORMOSIL glass matrix. [16]…”
Section: Enhanced Stable Activitymentioning
confidence: 99%
See 1 more Smart Citation